Genome wide adaptations of Plasmodium falciparum in response to lumefantrine selective drug pressure. - Mwai, L; Diriye, A; Masseno, V; Muriithi, S; Feltwell, T; Musyoki, J; Lemieux, J; Feller, A; Mair, G; Marsh, K; Newbold, C; Nzila, A; et al. (Public Library of Science, 2012)
The combination therapy of the Artemisinin-derivative Artemether (ART) with Lumefantrine (LM) (Coartem(R)) is an important malaria treatment regimen in many endemic countries. Resistance to Artemisinin has already been reported, and it is feared that LM resistance (LMR) could also evolve quickly. Therefore molecular markers which can be used to track Coartem(R) efficacy are urgently needed. Often, stable resistance arises from initial, unstable phenotypes that can be identified in vitro. Here we have used the Plasmodium falciparum multidrug resistant reference strain V1S to induce LMR in vitro by culturing the parasite under continuous drug pressure for 16 months. The initial IC(50) (inhibitory concentration that kills 50% of the parasite population) was 24 nM. The resulting resistant strain V1S(LM), obtained after culture for an estimated 166 cycles under LM pressure, grew steadily in 378 nM of LM, corresponding to 15 times the IC(50) of the parental strain. However, after two weeks of culturing V1S(LM) in drug-free medium, the IC(50) returned to that of the initial, parental strain V1S. This transient drug tolerance was associated with major changes in gene expression profiles: using the PFSANGER Affymetrix custom array, we identified 184 differentially expressed genes in V1S(LM). Among those are 18 known and putative transporters including the multidrug resistance gene 1 (pfmdr1), the multidrug resistance associated protein and the V-type H+ pumping pyrophosphatase 2 (pfvp2) as well as genes associated with fatty acid metabolism. In addition we detected a clear selective advantage provided by two genomic loci in parasites grown under LM drug pressure, suggesting that all, or some of those genes contribute to development of LM tolerance--they may prove useful as molecular markers to monitor P. falciparum LM susceptibility.